Viability of post acclimatized plantlets of Robusta coffee (Coffea canephora) after storage - Teguh Iman Santoso; Pudji Rahardjo (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2011)
This research related to the storage method of planting materials in the form of post acclimatized plantlets of Robusta coffee multiplied by somatic embryogenesis using plastic film that wraped the whole of plantlets. This information is important to support the delivery of clonal planting materials to distribution points, especially Robusta coffee plantlets viability based on condition of the container, storage period and density of plantlets. The research was conducted at Kaliwining Experimental Station of Indonesian Coffee and Cocoa Research Institute, located at 45 m asl. D rainfall type (Schmidt—Ferguson classification). The first experiment determind the effect of container condition and storage duration on viability of Robusta coffee plantlets. Each experimental unit contained 100 plantlets and each treatment was repeated three times with completely randomized design in factorial. The first factor was condition of storage container, i.e. airtight and non air tight. The second factor was storage period levels: 0, 5, 10, 15 and 20 days. The storage container was cardboard volume 11 dm3. The second experiment was conducted for the optimization of storage volume and storage period. Each treatment using 100 plantlets was repeated three times in completly randomized design with factorial. The first factor was storage volume of 7 dm3 and 11 dm3, the second factor was storage period levels: 0, 5, 10, 15 and 20 days. The results indicated that the maximum store period was obtained in an airtight storage treatment with 10 days, 96.3% plantlets viability, 1% fallen leaves, 3.3% water loss and not significantly different to control. For packing 100 plantlets with height 8—10 cm and leaf number 4—6 can use the volume of container store up to 7 dm3, which showed no significant difference to container volume 11 dm3 in the percentage of viability, the percentage of fallen leaves, loss of water. Key words : Robusta coffee, plantlets, storage, condition, period, viability.